(untitled) (Research, Society and Development, 2020)
The audiovisual movie Bacurau is a filmography that represents a utopian future for a community in Northeast Brazil with foreign interferences on its formation. The movie portrays the community’s position on the preservation of its historical and cultural heritage and the maintenance of its living memory. In this sense, it was sought to inquire what the State’s position, mainly the Municipal Public Administration, in the preservation of these themes on Small Communities based on the movie Bacurau. Thus, we had as specific objectives the notions of historical and cultural heritage based on legislation, applied to the film; in a second moment, we analyze the relationship between law and art that brings them to the subject of the right to memory and its maintenance by audiovisual movies; and in a third moment, the relationship between the right to memory, Bacurau’s artistic work and its intersections with the right / duty to protect the historical cultural heritage by the State and its role in protecting small communities was analyzed. The applied methodology is descriptive research, qualitative approach, bibliographic, documentary and audiovisual research and with an inductive method, based on the idea of the film for a general analysis of the State’s performance. We conclude that the work portrays the criticism of State action on the protection of historical-cultural heritage, where the notions of preservation of small communities are concerned and their memory is rarely addressed or insignificant in government policies, leaving the community itself to maintain its environment cultural environment where the State is absent.